1981
DOI: 10.3133/pp1185
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic U-Pb ages of zircon from the granitoids of the central Sierra Nevada, California

Abstract: Sixty-two samples from well-established comagmatic granitoid sequences and certain unassigned formations and plutons of the central part of the Sierra Nevada batholith between latitudes 37° and 38° N. have been dated by the isotopic U-Pb method on zircon. The U-Pb ages indicate the following age distribution of the granitoids: (1) The axial part of the batholith is occupied by Cretaceous granitoid sequences that are progressively younger eastward over a 37-m.y. interval extending from about 125 m.y. to about 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
146
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(154 citation statements)
references
References 26 publications
7
146
0
1
Order By: Relevance
“…The Sierran and Great Valley belts formed along the western margin of the North American plate, whereas the Franciscan was laid down on the approaching Farallon oceanic lithosphere. In northern California, the production of juvenile and reworked sialic crust was most voluminous in mid and Late Cretaceous time [Stern et al, 1981;Chen and Moore, 1982], but erosional debris from the dying calcalkaline arc was supplied to the fore arc and trench into Paleogene time [McLaughlin et al, 1982].…”
Section: Plate Tectonic Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Sierran and Great Valley belts formed along the western margin of the North American plate, whereas the Franciscan was laid down on the approaching Farallon oceanic lithosphere. In northern California, the production of juvenile and reworked sialic crust was most voluminous in mid and Late Cretaceous time [Stern et al, 1981;Chen and Moore, 1982], but erosional debris from the dying calcalkaline arc was supplied to the fore arc and trench into Paleogene time [McLaughlin et al, 1982].…”
Section: Plate Tectonic Implicationsmentioning
confidence: 99%
“…Dumitru et al (Early Cretaceous (circa 123 Ma) transition from nonaccretion behavior to strongly accretionary behavior within the Franciscan subduction complex, submitted to Tectonics, 2009) have suggested that the convergent margin was transformed from a nonaccretionary to an accretionary margin at $123 Ma. In any case, subsequent evolution of the continental margin involved the construction of three subparallel lithotectonic belts: (1) a massive Sierran batholith and its comagmatic but in-part earlier volcanic carapace [Stern et al, 1981;Bateman, 1992;Dunne et al, 1998;Irwin, 2003]; (2) a thick turbiditic section accumulating in the fore-arc basin as the Great Valley Group [Ingersoll, 1978[Ingersoll, , 1979[Ingersoll, , 1983Linn et al, 1992;DeGraaff-Surpless et al, 2002;Surpless et al, 2006;Wright and Wyld, 2007]; and (3) the rapidly deposited graywackes and intercalated dark shales of the Franciscan Complex in the offshore trench [Bailey et al, 1964[Bailey et al, , 1970Hamilton, 1969 et al, 2009]. The Sierran and Great Valley belts formed along the western margin of the North American plate, whereas the Franciscan was laid down on the approaching Farallon oceanic lithosphere.…”
Section: Plate Tectonic Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…1, 2, and 3). U/Pb zircon geochronology is the best tech nique for obtaining high-precision dates for gra nitic rocks to establish their crystallization ages (Stern et al, 1981).…”
Section: Introductionmentioning
confidence: 99%